An Analysis of Teaching English for Young Learners by Non English Pre-Service Teachers - Debby Yolanda Br Manullang; Trisnawati Harefa; Dennis Chandra; Darman Pangaribuan; Kartina Ramadhani Rambe (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study studied how pre-service teachers without English training taught young learners at SD Antasari Medan, Indonesia. The qualitative descriptive study comprised six PGSD pre-service teachers who volunteered to teach English without formal English training. Classroom observations, semi-structured interviews, and document analysis formed the basis for thematic analysis. The results demonstrated that teachers' general pedagogical skills helped them build pleasant learning spaces by greeting students, asking questions, motivating them, and planning Indonesian-English transitions. Teachers employed repetition, modelling, songs, pictures, gestures, and online resources to engage and instruct children. Due to their first language, pupils had problems reading, spelling, writing, and pronouncing words, and classroom management and evaluation were still poor. Transferable educational abilities helped, but they couldn't replace linguistic expertise. The study highlights the importance of focused professional development, improved instructional tools, and institutional support for primary school English teaching. The results also suggest that teacher education programs should better prepare non-English teachers for English instruction and encourage reflective practice. Comprehensive and longitudinal studies should examine non-specialist teaching's long-term consequences. Keywords: English for Young Leaners; Non-specialist English Teaching; Pedagogical Competence; Pre-service Teachers; Professional Development